간담관 질환에서 어소데옥시콜산 투여 요법 - 김혁; 유정주 (Taehan Ŭisa Hyŏphoe chi, 2024)
Background: This study aimed to summarize evidence of ursodeoxycholic acid (UDCA) use in the management of hepatobiliary diseases, present indications for UDCA use in Korea, and reimbursement criteria for UDCA use in the country. Current Concepts: UDCA is currently approved for the treatment and prevention of gallstone in obese patients with rapid weight loss after post-bariatric surgery, primary biliary cirrhosis (PBC), chronic liver disease with markedly elevated liver function test values, and chronic hepatitis C. However, the approval and reimbursement criteria for UDCA depend on the dose, specific diseases, and circumstances. UDCA is administered at doses of 100, 200, and 300 mg. The 100 mg dose is available over-the-counter, whereas a prescription is required for the 200 and 300 mg doses. The approval standards differed by dose: UDCA 100 mg for biliary diseases and chronic liver disease; UDCA 200 mg for gallstone, PBC, and chronic hepatitis C; and UDCA 300 mg for PBC, gallstone prevention in obese patients, and patients who had undergone gastrectomy. Co-administration of UDCA with antiviral drugs may require patients to bear some costs. UDCA can be combined with either milk thistle or biphenyl dimethyl dicarboxylate but not both. Discussion and Conclusion: UDCA is a relatively safe medication with many benefits. The current reimbursement standards for hepatobiliary diseases include chronic liver disease with elevated liver enzyme levels, gallstone, PBC, chronic hepatitis B, and chronic hepatitis C. Because UDCA is administered at varied doses, it is important to know the appropriate dose and regimen for each condition. KCI Citation Count: 0